2013
DOI: 10.1088/2041-8205/777/2/l25
|View full text |Cite
|
Sign up to set email alerts
|

ALMA CONTINUUM OBSERVATIONS OF A 30 Myr OLD GASEOUS DEBRIS DISK AROUND HD 21997

Abstract: Circumstellar disks around stars older than 10 Myr are expected to be gas-poor. There are, however, two examples of old (30-40 Myr) debris-like disks containing a detectable amount of cold CO gas. Here we present ALMA and Herschel Space Observatory observations of one of these disks, around HD 21997, and study the distribution and origin of the dust and its connection to the gas. Our ALMA continuum images at 886 µm clearly resolve a broad ring of emission within a diameter of ∼4. ′′ 5, adding HD 21997 to the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 31 publications
0
37
1
1
Order By: Relevance
“…However we will briefly describe these features, as they could potentially be observed with a high resolution instrument such as ALMA (e.g. Moór et al 2013;Dent et al 2014) or the HST (e.g. Golimowski et al 2011).…”
Section: Disc Overdensitiesmentioning
confidence: 99%
“…However we will briefly describe these features, as they could potentially be observed with a high resolution instrument such as ALMA (e.g. Moór et al 2013;Dent et al 2014) or the HST (e.g. Golimowski et al 2011).…”
Section: Disc Overdensitiesmentioning
confidence: 99%
“…This surprising result indicates that TW Hydrae is an old PMS star containing a massive gas disc that is several times the minimum mass required to make all the planets in our solar system. Even more recently, Roberge et al (2013) and Moór et al (2013) reported the discoveries of a low-mass protoplanetary-like gaseous disc, together with debris discs, around the older PMS stars 49 Ceti and HD 95086, with ages ranging from 10 Myr to 30 Myr. All these results support a scenario in which old and evolved debris discs still host a significant amount of gas and confirm our results with completely independent measurements.…”
Section: Spectral Energy Distributionsmentioning
confidence: 99%
“…This is supported by observations that planets are a common phenomenon in our galaxy, with an average of at least one planet per star (e.g., Cassan et al 2012) While it has been generally assumed that debris disks are devoid of molecular gas, detections of gas emission through millimeter-wavelength spectroscopy date back at least two decades (Zuckerman et al 1995;Dent et al 2005), and absorption line spectroscopy in edge-on debris disks has also identified the presence of a circumstellar gas component around a number of different stars (Crawford et al 1994;Roberge et al 2002;Chen & Jura 2003;Redfield 2007). Millimeterwavelength interferometry provided the first spatially resolved observations of the molecular gas emission in a debris disk (Hughes et al 2008a), and the improved sensitivity and angular resolution of the Atacama Large Millimeter/submillimeter Array (ALMA) has led to a resurgence of interest in these objects, resulting in spectacular gas and dust imaging of the recently discovered HD 21997 disk Moór et al 2013), the iconic β Pictoris disk (Dent et al 2014), and recently the first gas-bearing debris disk around a solar-type star (HD 181327; Marino et al 2016). Another object of interest has been the optically thin dust disk around the 5 Myr old Herbig Ae star HD 141569, whose classification as a transitional or debris disk has been an object of intense discussion in the literature: recent observations with the Submillimeter Array (SMA) and Combined Array for Research in Millimeter-wave Astronomy (CARMA) have spatially resolved the gas disk for the first time (Flaherty et al 2016), and ALMA observations probe the disk in greater detail (White et al 2016).…”
Section: Introductionmentioning
confidence: 99%